Heat and mass transfer of water‐based copper and alumina hybrid nanofluid over a stretching sheet. Issue 2 (4th October 2022) - Mishra, Swetapadma; Swain, Kharabela; Dalai, Renuprava
Abstract: Hybrid nanofluids (HNFs) are vital in engineering and industrial applications due to significant effective thermal conductivity as compared with regular fluid and nanofluid (NF). The HNF is a process of the conglomeration of two or more nanoparticles of different thermophysical properties to affect the thermal transport characteristics of base fluid, particularly in gearing up heat switch charge. Further, the impact of HNF combined with stretching and squeezing of bounding surface has direct application in thinning/thickening of polymeric sheets in the chemical industry. The current study analyzes the flow of HNF over a stretching sheet under the influence of chemical reaction as well as suction/injection. We have considered water ( H 2 O ) $({{\rm{H}}}_{2}{\rm{O}})$ as the base fluid and copper ( Cu ) $(Cu)$, and aluminum oxide ( Al 2 O 3 ) $(Al_{2}{{\rm{O}}}_{3})$ as nanoparticles. The consequences of the magnetic field, viscous dissipation, and Joule heating are also to be investigated. The resulting partial differential equations are transformed into nonlinear ordinary differential equations using suitable similarity transformations. The numerical solutions to governing equations are obtained with the help of MATLAB software using the bvp4c solver. The important finding is: the rate of heat transfer of HNF is higher than that of NF as well as base fluid. Moreover, contributions of higher Eckert number and radiation parameter are to increase the temperature in the flow domain, whereas the Prandtl number reduces it. It is further noticed that heavier species as well as viscous dissipation decline the level of concentration across the flow field.